Exploring the determinants of wine export performance. Analyzing the importance of noneconomic performance - Santos, F.; Dias, Á.; Pereira, L.; Lopes da Costa, R.; Gonçalves, R. (Academia Revista Latinoamericana de Administracion, 2023)
Purpose – The wine sector is a growing industry with an important share of the revenue resulting from export markets. Due to its cultural nature, wine exporting requires specific firm and managerial capabilities. As such, traditional approaches to the factors influencing export performance must integrate the specificities of wine as a product. Design/methodology/approach – This study, based on a sample of 93 wine producers, develops and tests, using structural equation modeling, specifically the partial least squares method, a conceptual model of the influence of internal factors, external factors and partner relationship capabilities in export performance. Findings – Results reveal that internal factors and partner relationships have an impact on the firm’s noneconomic performance which influences economic performance. It is also shown by the results that external factors do not affect the noneconomic performance or economic performance. Moreover, the results show the moderation effect of the noneconomic variable. Internal factors and relationship capabilities have an impact on economic performance considering the mediation effect of the noneconomic performance. Overall, firms’ internal factors and relationship capabilities are crucial to achieve better export performance for Portuguese wine companies. Originality/value – This study combines the theories of SCP, resource-based view and relational or behavior perspective to present a novel approach to export performance by analyzing the external and internal dimensions of the firm in relation to both financial and nonfinancial performances.